Population Dynamics of Listeria monocytogenes and Yeast and Mold Levels on Different Pear Varieties During Simulated Storage - Mengqian Hang; Edmund Larbi Afari; Xiaoye Shen; Yuan Su; Manoella Mendoza; Ines Hanrahan; Mei-Jun Zhu (Foods)
This study examined the attachment, persistence, and fate of Listeria monocytogenes on selected varieties of fresh pears during simulated extended storage, along with the dynamics of resident yeast and mold (Y&M) populations. Following inoculation with ~7.0 log CFU/mL, L. monocytogenes exhibited varying attachment efficiencies across pear varieties, resulting in 6.23 ± 0.03, 6.30 ± 0.01, and 5.12 ± 0.01 log CFU/pear on Bartlett, d’Anjou, and Bosc pears, respectively, after 24 h. The L. monocytogenes population gradually declined on pear surfaces during storage. After 14 days, L. monocytogenes populations decreased to ~4.20, 5.96, and 4.07 log CFU/pear on Bartlett, d’Anjou, and Bosc pears, respectively, regardless of temperature, and remained stable over the subsequent 14 days. During 20-week storage at 0 °C, the L. monocytogenes level decreased by 2.65–3.84 log CFU/pear on all pear varieties. Y&M levels varied across pear varieties and crop years. The initial Y&M counts for Bartlett, d’Anjou, and Bosc in year 2 were 4.37 ± 0.01, 5.93 ± 0.02, and 5.11 ± 0.03 log CFU/pear, respectively. The Y&M levels of d’Anjou and Bosc for years 1 and 2 were 4.73–4.79 and 5.11–5.93 log CFU/pear, respectively. During 20-week storage at 0 °C, Y&M counts generally increased, with Bartlett pears exhibiting a more pronounced rise after 12 weeks. Data indicated that L. monocytogenes did not grow on pears; instead, its population declined under all simulated storage conditions, offering practical guidance for pear packers on Listeria behaviors under various storage conditions.